2015
DOI: 10.15252/embj.201591884
|View full text |Cite
|
Sign up to set email alerts
|

Departure gate of acidic Ca 2+ confirmed

Abstract: More potent, but less known than IP3 that liberates Ca2+ from the ER, NAADP releases Ca2+ from acidic stores. The notion that TPC channels mediate this Ca2+ release was questioned recently by studies suggesting that TPCs are rather PI(3,5)P2‐activated Na+ channels. Ruas et al (2015) now partially reconcile these views by showing that TPCs significantly conduct both cations and confirm their activation by both NAADP and PI(3,5)P2. They attribute the failure of others to observe TPC‐dependent NAADP‐induced Ca2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…Another study hints towards a convergent regulation of TPC2 by Mg 2+ , NAADP, PI(3,5)P 2 and two protein kinases (JNK and p38) ( Jha et al, 2014 ). A very recent study confirmed that TPCs conduct both Ca 2+ and Na + ions and that they are activated by NAADP as well as PI(3,5)P 2 ( Ruas et al, 2015 ; Jentsch et al, 2015 ). The biological relevance of two-pore channels was recently highlighted by a report showing that TPCs are crucial to successful infection of host cells by the Ebola virus and that disruption of TPC function leads to halted virus trafficking ( Sakurai et al, 2015 ).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Another study hints towards a convergent regulation of TPC2 by Mg 2+ , NAADP, PI(3,5)P 2 and two protein kinases (JNK and p38) ( Jha et al, 2014 ). A very recent study confirmed that TPCs conduct both Ca 2+ and Na + ions and that they are activated by NAADP as well as PI(3,5)P 2 ( Ruas et al, 2015 ; Jentsch et al, 2015 ). The biological relevance of two-pore channels was recently highlighted by a report showing that TPCs are crucial to successful infection of host cells by the Ebola virus and that disruption of TPC function leads to halted virus trafficking ( Sakurai et al, 2015 ).…”
Section: Resultsmentioning
confidence: 86%
“…The mechanisms responsible for Ca 2+ filling and release from these acidic stores are not yet fully understood. The main players involved in lysosomal calcium release and signaling are transient receptor potential (TRP) channels such as mucolipin 1 (TRPML1) ( Pryor et al, 2006 ) and two two-pore channels (TPC1 and TPC2), which are thought to be Ca 2+ channels activated by nicotinic acid adenine dinucleotide phosphate (NAADP), Mg 2+ or phosphatidylinositol 3,5-bisphosphate (PI(3,5)P 2 ) ( Brailoiu et al, 2009 ; Wang et al, 2012 ; Ruas et al, 2014 ; Brailoiu et al, 2010 ; Rybalchenko et al, 2012 ; Pitt et al, 2010 ; Pitt et al, 2014 ; Jha et al, 2014 ; Ruas et al, 2015 ; Jentsch et al, 2015 ). A very recent study showed that lysosomal calcium signaling regulates autophagy through the actions of the phosphatase calcineurin and the transcription factor EB (TFEB) ( Medina et al, 2015 ) which places the lysosome at the center of this very important signaling hub and underlines the importance of understanding the regulation of lysosomal calcium signaling.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that this channel might be primarily a sodium channel activated by PI(3,5)P 2 (Wang et al, 2012). Although this remains controversial, it appears that at least under some conditions the TPC2 channel in the lysosomal membrane can conduct Ca 2+ as a consequence of actions of NAADP Jentsch et al, 2015).…”
Section: Are the Effects Of Naadp In Cardiac Myocytes Dependent On Tpc2?mentioning
confidence: 99%
“…Although the physiological functions of TPCs are not well understood, it is assumed that they are involved in the regulation of endocytosis and endo-lysosomal vesicle trafficking, i.e. of sorting and fusion events during protein uptake, protein recycling and degradation 6 8 . Trafficking between lysosomes, trans-Golgi network and the plasma membrane via endosomes and transport vesicles is tightly regulated by locally restricted Ca 2+ release from acidic stores 2 .…”
Section: Introductionmentioning
confidence: 99%